2016
DOI: 10.1111/bjd.14868
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of patient‐reported outcomes in patients with cutaneous lupus erythematosus

Abstract: Cutaneous lupus erythematosus (CLE) is a chronic dermatological autoimmune disease marked by photosensitive lesions that can lead to hyperpigmentation changes, scarring and hair loss. Health-related quality of life (HRQoL) in patients with CLE is severely impaired. Given the heterogeneous nature of CLE, health perceptions of patients can differ significantly from those of clinicians. It is important to use subjective measures, such as patient-reported outcomes (PROs), to capture HRQoL data in patients with CLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 76 publications
(224 reference statements)
1
24
0
Order By: Relevance
“…The finding of diminished QoL for female vs. male patients is consistent with that in the literature, even if different health‐related QoL measurement instruments were used, and concordant with a similar finding for other cutaneous diseases (greater psychiatric comorbidities and a worse QoL in women than in men).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…The finding of diminished QoL for female vs. male patients is consistent with that in the literature, even if different health‐related QoL measurement instruments were used, and concordant with a similar finding for other cutaneous diseases (greater psychiatric comorbidities and a worse QoL in women than in men).…”
supporting
confidence: 90%
“…It is unsurprising that generalized disease has a greater impact on QoL than milder or localized forms, similarly to the case with other dermatological conditions. In other studies, QoL deterioration was demonstrated with a corresponding increase in CLE activity …”
mentioning
confidence: 64%
See 1 more Smart Citation
“…Currently, there are a limited number of PRO measures used in patients with CLE. Findings from a systematic review reported that the QoL instruments commonly used in patients with CLE are Dermatology Life Quality Index (DLQI), Skindex‐29, Short Form 36 (SF‐36) and visual analogue scales (VASs) . However, because patients with CLE were not involved in the development of these instruments, these measures may not capture all issues relevant to CLE.…”
mentioning
confidence: 99%
“…To depict our current understanding of the QoL of patients with CLE, Ogunsanya et al . performed a comprehensive, systematic review of QoL studies in patients with CLE.…”
mentioning
confidence: 99%